Information Technology to Support E-Advertisement - W Novianti; E Erdiana (International Journal of Research and Applied Technology (INJURATECH), 2021)
This study aims to determine the benefits of social media as a supporter of advertising activity in a business. This study used descriptive qualitative method with literature study by collecting a variety of data related to what is researched, then analyze and summarize so that researchers can explain what are the benefits of social media that can support the advertising activities. Results from this study is the social media provides many benefits to the business world and can be made in one of the media that support the advertising activities for a business. Nowadays anyone can do a business and expand global business network by simply using social media